Clinical and radiographic evaluation of the Periodontium with biologic width invasion - Bruna Almeida Silva Carvalho; César Augusto Barroso Duarte; Jaciara Fagundes Silva; Walter Winícius da Silva Batista; Dhelfeson Willya Douglas-de-Oliveira; Evandro Silveira de Oliveira; Luana de Goés Soares; Endi Lanza Galvão; Gabriela Rocha-Gomes; José Cristiano Ramos Glória; Patrícia Furtado Gonçalves; Olga Dumont Flecha (BMC Oral Health, 2020)
Abstract Background The biologic width is defined as the coronal dimension to the alveolar bone that is occupied by healthy gingival tissue. The objective of the present study was to correlate radiographic findings of biologic width invasion with the periodontium status. Methods It were included 14 patients with restored teeth with biological width invasion, on the proximal sites, observed clinically and radiographically. 122 proximal sites were evaluated, 61 in the test group (biological width invasion) and 61 in the control group (adequate biological width). Smokers and patients presenting periodontal disease or restorations with contact in eccentric movements, horizontal over-contour or secondary caries were excluded from the sample. The invasion of the biologic width was diagnosed when the distance from the gingival margin of restoration to the bony crest was less than 3 mm. Intrabony defect and bone crest level, as well as, their vertical and horizontal components were radiographically evaluated when present. Plaque index, bleeding on probing, probing depth, gingival recession height, keratinized gingival height and thickness, and clinical attachment level were clinically evaluated. Data were subjected to Spearman’s Correlation and Wilcoxon’s test. Result The most prevalent tooth with biological width invasion was the first molar. There was a statistically significant correlation between the bone crest (p < 0.001), vertical (p < 0.001) and horizontal (p = 0.001) components. In the test group, there was a statistically significant correlation between bleeding on probing (p < 0.001; r = 0.618) and width of gingival recession (p = 0.030; r = − 0.602) with the intraosseous component; and between keratinized gingival height and bone level (p = 0.037; r = − 0.267). In the control group, there was a correlation between plaque index (p = 0.027; r = − 0.283) with bone level and correlation between keratinized gingival thickness and bone level (p = 0.034; r = − 0.273) and intrabony component (p = 0.042; r = 0.226). Conclusion A statistically significant relationship was found between bleeding on probing and gingival recession in patients who presented intrabony defects due to the invasion of biological width, which may be also related to the thickness of the keratinized gingiva.